The use of mathematical Modeling and linear programming in agribusiness - Jandrić Mersida; Vico Grujica; Nedeljković Miroslav (Trendovi u Poslovanju)
This study focuses on the theoretical analysis of the application of modeling and mathematical, particularly linear programming, in managerial processes within the agro-industrial complex. The authors have dedicated themselves specifically to defining planning processes, classifying models, and organizing production structures, including vertical and horizontal structures. Despite the fact that the benefits of linear programming have been proven, it is still not widely accepted and applied in our region. The reasons for this can be found in the relative complexity of the process, both in creating logical and mathematical models, and in interpreting results. Although there are specialized software and add-ons such as Solver in MS Excel, they are still not accessible enough to a wider range of users in the agro-industrial sector. It is evident that there is a need for the development of new specialized software solutions with user-friendly interfaces, which would make them more accessible, primarily to advisors, and then to agricultural producers.